What Do We See When Looking at China's Engagements in Africa? An Analysis of Mainstream Academic Perspectives. Issue 135 (4th May 2022) - Ding, Jin; Ratz, Christoph; Bergman, Manfred Max
ABSTRACT: Since China initiated the Go Out (走出去战略) policy in 1999, its increasing presence and influence in Africa have led to controversial debates among scholars. This article systematizes the different perspectives on the relationship between Africa and China in the contemporary academic literature, and how these debates differ from representations of Africa's relations with Western actors. Based on Content Configuration Analysis, the results indicate that China in Africa is constructed in relation to Africa and the West. Academic papers tend to impose a Western perspective on China's involvement with Africa, most notably marked by neo-colonialism and development cooperation. This research highlights the shortcomings, limitations, and risks of this Eurocentric approach, and outlines alternatives to better understand China's engagement in and with Africa.